Time for a paradigm shift? Exploring competition regulation and its relationship with the rising global burden of industrial epidemics - Benjamin Wood; Sven Gallasch; Nicholas Shaxson; Katherine Sievert; Gary Sacks (Health Economics, Policy and Law)
Competition regulation plays a key role in determining firm size, market structure, and what firms can do with their market power. In this paper, we explore how competition regulation in many countries has largely tolerated rising industry concentration and market power in harmful consumer product industries, which, in turn, has likely facilitated an increase in preventable death and disease associated with such industries (ie. industrial epidemics). One important reason for this tolerance has been the rise of the ‘consumer welfare’ standard, which contends that competition regulators should only focus on a narrow set of concerns mostly relating to consumer price and output. Yet, recent developments shed light on potential avenues through which competition regulation could work more synergistically with public health policies and programmes. While discussions on how to leverage competition regulation along these lines are invariably contested and complex, we argue that it is critical that public health advocates engage with these discussions.